PEMBINAAN EKSTRAKURIKULER OLAHRAGA DI SEKOLAH DASAR ISLAM AL-AZHAR 14 SEMARANG TAHUN AJARAN 2012/2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
Background Issues about Sport extracurricular development of Elementary School (SD) Al-Azhar 14Semarang got some feats as the result of sport extracurricular development. Sport extracurricular developmentneeds an organisation , development pattern, exercise program and instrument. The research focus of this caseis